Retinal changes in patients with idiopathic inflammatory myopathies: A case-control study in the MyoCite cohort - Rachna Aggarwal; R. Naveen; Darpan Thakare; Rohit Shahi; Anamika Kumari Anuja; Ahmad Husain; Maryam Abbasi; Upendra Rathore; Vikas Agarwal; Latika Gupta; Latika Gupta; Latika Gupta; et al. (Frontiers in Medicine, 2022)
BackgroundRetinal changes are the window to systemic vasculature. Therefore, we explored retinal changes in patients with Idiopathic inflammatory myopathies (IIM) as a surrogate for vascular health.MethodsAdult and Juvenile IIM patients (2017 ACR/EULAR criteria), visiting a tertiary care center in 2021 were enrolled for detailed ophthalmic examination in comparison with healthy controls (HC). Patients with conditions that precluded thorough posterior chamber examination were excluded. Scale variables are expressed as median (IQR). Multivariate analysis (binary logistic regression-BLR) was conducted, adjusting for age, gender, and comorbidities besides factors significant in univariate analysis.Results43 patients with IIM [31 females; age 36 (23–45) years; disease duration 5.5 (2-12) months] were enrolled for participation. DM (44%) was the most common diagnosis. IIM patients exhibited frequent attenuation of retinal vessels (32.6 vs. 4.3%, p < 0.001), AV nicking (14 vs. 2.2%, p = 0.053), and vascular tortuosity (18.6 vs. 2.2%, p = 0.012), besides decreased visual acuity (53.5 vs. 10.9%, p<0.001) and immature cataracts (34.9 vs. 2.2%, p < 0.001). Attenuation of vessels [OR 10.9 (1.7–71), p = 0.004] emerged as significantly different from HC after adjusting for covariates in BLR. Notably, adults with IIM were more predisposed to retinal abnormalities [21 (57%) vs. 1 (16%), p = 0.068], especially attenuation of vessels [14(38%) vs. 0(0), p = 0.067] than jIIM. However, no difference was found in retinal features amongst the subtypes of adult IIM, nor did they correlate with MDAAT, MDI, or HAQ-DI.ConclusionRetinal microvasculopathy and diminution of vision occur in nearly one-thirds to half of the patients with IIM. Microvasculopathy occurs across subtypes of IIM, and more so in adults, calling for further investigation as a surrogate for damage assessment and potentially even systemic vascular health.